Overcoming the Challenges Associated with Image‐Based Mapping of Small Bodies in Preparation for the OSIRIS‐REx Mission to (101955) Bennu. Issue 12 (21st December 2018) - DellaGiustina, D. N.; Bennett, C. A.; Becker, K.; Golish, D. R.; Le Corre, L.; Cook, D. A.; Edmundson, K. L.; Chojnacki, M.; Sutton, S. S.; Milazzo, M. P.; Carcich, B.; Nolan, M. C.; et al.
Abstract: The OSIRIS‐REx Asteroid Sample Return Mission is the third mission in National Aeronautics and Space Administration (NASA)'s New Frontiers Program and is the first U.S. mission to return samples from an asteroid to Earth. The most important decision ahead of the OSIRIS‐REx team is the selection of a prime sample‐site on the surface of asteroid (101955) Bennu. Mission success hinges on identifying a site that is safe and has regolith that can readily be ingested by the spacecraft's sampling mechanism. To inform this mission‐critical decision, the surface of Bennu is mapped using the OSIRIS‐REx Camera Suite and the images are used to develop several foundational data products. Acquiring the necessary inputs to these data products requires observational strategies that are defined specifically to overcome the challenges associated with mapping a small irregular body. We present these strategies in the context of assessing candidate sample sites at Bennu according to a framework of decisions regarding the relative safety, sampleability, and scientific value across the asteroid's surface. To create data products that aid these assessments, we describe the best practices developed by the OSIRIS‐REx team for image‐based mapping of irregular small bodies. We emphasize the importance of using 3‐D shape models and the ability to work in body‐fixed rectangular coordinates when dealing with planetary surfaces that cannot be uniquely addressed by body‐fixed latitude and longitude. Plain Language Summary: The OSIRIS‐REx Asteroid Sample Return Mission must map asteroid (101955) Bennu using the OSIRIS‐REx Camera Suite. Here we present the techniques that are established to accomplish this goal. Mapping helps us find the best place on the surface of Bennu from which to gather a sample. Because asteroids are small bodies with weak gravitational fields, maneuvering a spacecraft around them can be challenging. Considering these complexities, we have found ways to gather images of Bennu needed for creating maps. Additionally, due to the irregular shape of many asteroids, producing 2‐D maps in terms of latitude and longitude may be insufficient for describing their surface geography. To that end, we have developed software that is capable of creating and displaying image maps in 3‐D. Key Points: The OSIRIS‐REx Asteroid Sample Return Mission performs image‐based mapping of (101955) Bennu to aid in the selection of a sample‐site We develop observational strategies to perform mapping to address the challenges associated with surveying a small body We identify pitfalls and best practices for mapping images of small bodies with large concavities, elongated axes, or overhanging terrain